2013
DOI: 10.1002/smll.201201770
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput‐Per‐Footprint Inertial Focusing

Abstract: Matching the scale of microfluidic flow systems with that of microelectronic chips for realizing monolithically integrated systems still needs to be accomplished. However, this is appealing only if such re-scaling does not compromise the fluidic throughput. This is related to the fact that the cost of microelectronic circuits primarily depends on the layout footprint, while the performance of many microfluidic systems, like flow cytometers, is measured by the throughput. The simple operation of inertial partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 34 publications
7
61
2
Order By: Relevance
“…For example, these side streaks emerge at certain Re C values that scale with ,l 0.4 (,105 for l 5 0.066, ,140 for l 5 0.149 and ,180 for l 5 0.225). The existence of these side streaks also concurs with the decrease in positive lift coefficient found at increasing Re C [33][34][35] . The formation of these side streaks also indicates the limited distance over which the lateral wall effect forces are dominant.…”
Section: Resultssupporting
confidence: 79%
“…For example, these side streaks emerge at certain Re C values that scale with ,l 0.4 (,105 for l 5 0.066, ,140 for l 5 0.149 and ,180 for l 5 0.225). The existence of these side streaks also concurs with the decrease in positive lift coefficient found at increasing Re C [33][34][35] . The formation of these side streaks also indicates the limited distance over which the lateral wall effect forces are dominant.…”
Section: Resultssupporting
confidence: 79%
“…5B). Experiments at much higher Reynolds numbers have shown that additional focusing positions appear in channel corners [28,29], but we find no evidence of alternate focusing positions over the range Re = 30 − 180.…”
Section: Dependence Of Focusing Forces On Particle Size and Reynolds contrasting
confidence: 81%
“…3 New applications have since emerged, with inertial focusing in particular, leading to new methods for high-throughput cytometry. [4][5][6][7][8][9][10] More recently, fluid sculpting via inertial flow has been demonstrated through so-called "pillar programming." 11,12 See Fig.…”
Section: Introductionmentioning
confidence: 99%